Molecular Fingerprint of Amphioxus Frontal Eye Illuminates the Evolution of Homologous Cell Types in the Chordate Retina - Pergner, Jiri; Vavrova, Anna; Kozmikova, Iryna; Kozmik, Zbynek (Frontiers in Cell and Developmental Biology, 2020)
The evolution of the vertebrate eye remains so far unresolved. Amphioxus frontal eye pigment cells and photoreceptors were proposed to be homologous to vertebrate photoreceptors and retinal pigmented epithelium, based on ultrastructural morphology and gene expression analysis in B. floridae. Here, we present comparative molecular data using two additional amphioxus species, a closely related B. lanceolatum, and the most divergent A. lucayanum. Taking advantage of a unique set of specific antibodies we characterized photoreceptors and putative interneurons of the frontal eye and investigated its neuronal circuitry. Our results corroborate generally conserved molecular fingerprint among cephalochordate species. Furthermore, we performed pharmacological perturbations and found that the Notch signaling pathway, a key regulator of retina development in vertebrates, is required for correct ratios among frontal eye cell types. In summary, our study provides a valuable insight into cell-type relationships in chordate visual organs and strengthens the previously proposed homology between amphioxus frontal eye and vertebrate eyes.